Relationship Between Blood- and Cerebrospinal Fluid–Bound Neurotransmitter Concentrations and Conditioned Pain Modulation in Pain-Free and Chronic Pain Subjects - Parent, Alexandre J; Beaudet, Nicolas; Daigle, Kathya; Sabbagh, Robert; Sansoucy, Yanick; Marchand, Serge; Sarret, Philippe; Goffaux, Philippe (The journal of pain, 2015)
Abstract Descending pain inhibition is an endogenous pain control system thought to depend partially on the activation of bulbospinal monoaminergic pathways. Deficits in descending pain inhibition have been reported in numerous human chronic pain conditions, but there is currently no consensus regarding the neurochemical correlates responsible for this deficit. The aims of this study were to 1) assess the efficacy of descending pain inhibition in pain-free and chronic pain subjects, 2) screen for changes in centrally (ie, cerebrospinal fluid) and peripherally (ie, plasma) acting monoamine concentrations, and 3) explore the relationship between descending pain inhibition and monoamine neurotransmitter concentrations. Our results clearly show a deficit in pain inhibition, along with lower plasma norepinephrine and metanephrine concentrations in chronic pain subjects, compared to pain-free subjects. No differences were found in cerebrospinal fluid neurotransmitter concentrations. Finally, our results revealed a positive relationship between blood-bound norepinephrine and metanephrine concentrations and the efficacy of descending pain inhibition. Thus, basal monoamine levels in blood were related to descending pain inhibition. This finding supports the emerging idea that individual differences in descending pain inhibition may be linked to individual differences in peripheral processes, such as monoamines release in blood, which are possibly related to cardiovascular control. Perspectives This article presents psychophysical and neurochemical findings that indicate that the latent potential of descending pain inhibitory responses is associated with differential activity in peripheral processes governed by monoamine neurotransmitter release, bringing insights into the relationship between descending pain inhibition and cardiovascular control in humans.